Appraisal of literature reviews on end-of-life care for minority ethnic groups in the UK and a critical comparison with policy recommendations from the UK end-of-life care strategy - Evans, Natalie (BioMed Central, 2011)
BACKGROUND: Evidence of low end-of-life (EoL) care service use by minority ethnic groups in the UK has given rise to a body of research and a number of reviews of the literature. This article aims to review and evaluate literature reviews on minority ethnic groups and EoL care in the UK and assess their suitability as an evidence base for policy. METHODS: Systematic review. Searches were carried out in thirteen electronic databases, eight journals, reference lists, and grey literature. Reviews were included if they concerned minority ethnic groups and EoL care in the UK. Reviews were graded for quality and key themes identified. RESULTS: Thirteen reviews (2001-2009) met inclusion criteria. Seven took a systematic approach, of which four scored highly for methodological quality (a mean score of six, median seven). The majority of systematic reviews were therefore of a reasonable methodological quality. Most reviews were restricted by ethnic group, aspect of EoL care, or were broader reviews which reported relevant findings. Six key themes were identified. CONCLUSIONS: A number of reviews were systematic and scored highly for methodological quality. These reviews provide a good reflection of the primary evidence and could be used to inform policy. The complexity and inter-relatedness of factors leading to low service use was recognised and reflected in reviews' recommendations for service improvement. Recommendations made in the UK End-of-Life Care Strategy were limited in comparison, and the Strategy's evidence base concerning minority ethnic groups was found to be narrow. Future policy should be embedded strongly in the evidence base to reflect the current literature and minimise bias.